Impact of Big Data Products on the Entrepreneurial Performance of E-Commerce Farmers: Evidence from China - Yiwu Zeng; Lili Li; Baogang Li; Huanxin Gong; Guojun Zhang (SAGE Open)
Rural e-commerce, dominated by entrepreneurial farmers, is growing rapidly in developing countries, especially in China. However, with the expanding scale of e-commerce farmers, the competition is becoming fierce, and their entrepreneurial performance is facing difficulties in growth. Pioneering practices in China show that big data can promote the sustainable development of e-commerce farmers. This paper attempts to explore how big data products affect e-commerce farmers’ entrepreneurial performance by using the survey data from China, and structural equation modeling. Findings show that big data products significantly improve e-commerce farmers’ entrepreneurial performance. The usefulness and ease of use of and experience with big data products can enhance e-commerce farmers’ entrepreneurial alertness and dynamic capabilities. The findings have important implications for how to promote entrepreneurial growth of e-commerce farmers and big data applications in rural areas.